Rural landscape shaping through the introduction of trees in land consolidation projects in Poland - Sobolewska-Mikulska, Katarzyna; Stańczuk-Gałwiaczek, Małgorzata (International Conference “Environmental Engineering”, 2017)
Land consolidation works carried out in Poland are mainly aimed at the improvement of spatial structure of plots in agricultural holdings. However, modern trends indicate the necessity of compliance with sustainable rural development policy. This implicates the inevitability of inclusion of the environmental, landscape, technical and organizational aspects in the land consolidation projects in Poland. One such operation is the introduction of trees and shrubs. The paper aims to investigate the scope of land consolidation design solutions concerning the introduction of trees and shrubs. The study was based on selected land consolidation projects from different regions of Poland. The paper also proposes the concept of implementation of the design solutions related to the introduction of trees and shrubs in the land consolidation projects.
Keywords: introduction of trees and shrubs; land consolidation project; rural areas in Poland